Indiana Jones and the dial of destiny [videorecording (Blu-Ray)] - Mangold, James; Butterworth, Jez; Butterworth, John-Henry, 1976-; Koepp, David; Ford, Harrison, 1942-; Waller-Bridge, Phoebe, 1985-; Banderas, Antonio; Allen, Karen, 1951-; Rhys-Davies, John; Wilson, Shaunette Renée, 1990-; Kretschmann, Thomas, 1962-; Jones, Toby, 1966-; et al. (Lucasfilm Ltd., 2023)
Daredevil archaeologist Indiana Jones races against time to retrieve a legendary dial that can change the course of history. Accompanied by his goddaughter, he soon finds himself squaring off against Jürgen Voller, a former Nazi who works for NASA.